O violão na cidade de Goiânia: trajetória histórica, principais personagens - Furtado, Fernanda Vasconcelos (2016)
This research aims to investigate the historical background and the several interactions developed for the guitar in the city of Goiânia and its Metropolitan region, from the 1930s to the present time. The main characters, the works and actions related to the historical trajectory of this musical instrument and its actors stood out in this process, with emphasis on the inherited culture. A methodology with qualitative and quantitative approaches from primary and secondary sources was used, based on facts and stories experienced by several generations. Such information was cataloged, selected and analyzed in order to build a historical narrative not yet unveiled.